Inovação no Setor de Serviços em São Caetano do Sul (SP): Mensuração e Oportunidades de Desenvolvimento Local - Raul Gomes Pinheiro (Universidade Regional do Noroeste do Estado do Rio Grande do Sul, 2015)
This study aims to measure the innovation degree and verify influencing factors on innovation of 164 micro and small enterprises in services sector in São Caetano do Sul, in city of the Metropolitan Region of São Paulo. Binary Logistic Regression was used to support the quantitative analysis. It was found that the degree of innovation was 0.109, with 34.9% of companies surveyed with no evidence of innovation. Four factors are most relevant to the classification of micro and small companies as innovative: search suppliers; use of formal credit source; training and payment policy and employee benefits. The greater the intensity of the practice of procedures and behavior illustrated by the above factors, the greater the likelihood the company integrate the innovative group. The results obtained pointed out thatinnovation is not a priority element in the agenda of entrepreneurs, which can be seen on the fact of most the searched companies did not adopt practices that could characterize them as innovative.